Keterkaitan Faktor Electronic Word of Mouth dan Aksesibiltas dengan keputusan berkunjung Di Umbul Kemanten Klaten - Gentah Sulfindarnarko; Kiki Rizki Makiya; Moch. Nur Syamsu (Journal of Tourism and Economic, 2024)
This study aims to analyze how the e-WoM factor and accessibility affect tourists' visiting decisions at Umbul Kemanten. This research uses quantitative methods by involving 100 tourists as respondents. Data were analyzed using multiple linear regression analysis. The results showed that e-WOM has a positive and significant influence on visiting decisions, and accessibility also affects visiting decisions. These findings are expected to improve promotional strategies on social media and accessibility to increase tourist visits at Umbul Kemanten Klaten.